Handbook of cathodic corrosion protection theory and practice of electrochemical protection processes - Baeckmann, W. von (Walter); Schwenk, W. (Wilhelm); Prinz, W.; Baeckmann, W. von (Walter). (Houston, Tex. : Gulf Pub. Co., 1997)
This comprehensive handbook covers all aspects of cathodic protection in terms of both practice and theory.
Historic development of corrosion protection. Fundamentals and concepts of corrosion and electrochemical corrosion protection. Fundamentals and practice of electrical measurements. Corrosion in water and soil. Corrosion protection by coatings and cladding. Sacrificial anodes. Impressed current anodes. Impressed current installations and protective current instruments. Impressed current installations in the ground and influential factors. Pipelines. Storage containers and storage tanks. Local cathodic protection. Telephone cable. Power cables. Influence of stray current and stray current protection. Marine buildings and offshore pipelines. Cathodic protection of ships. Cathodic protection of borehole piping. Cathodic protection of reinforcing steel in concrete structures. Internal cathodic protection of water tanks. Electrochemical corrosion protection for internal surfaces of apparatus, containers, and pipes. Safety and economy. Effect on long conducting pipelines of high voltage installations. Current and voltage distribution in a stationary electric field.
Translation of: Handbuch des kathodischen Korrosionsschutzes, 3rd ed. 1989.
Rev. ed. of: Handbook of cathodic protection / [by] W. v. Baeckmann. 1975.
Includes bibliographical references and index.
Keywords: Cathodic protection -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc